Visualisasi Simbol Iklan di Media Televisi (Suatu Kajian Teori Semiotik dan Hermeneutik) - Siti Maemunah (Rekam: Jurnal Fotografi, Televisi, Animasi)
Observing about advertisement and the language used in advertisement in mass communication media needs deeply understanding and knowledge. Thephenomenon of advertisement in mass media sometimes used as tools in order to satisfy human’s needs, whether is primary, secondly and so on. In a higher level, there could be a multilevel advertisement which is used as a “vehicle “ to persuasively invite the audiens to concern about the matters they recite such as political, enonomical, social, and cultural as well.